2017
DOI: 10.1620/tjem.242.129
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Levels of miR-29c-3p and miR-19b-3p as Biomarkers for Alzheimer’s Disease

Abstract: MicroRNAs (miRNAs) are short noncoding RNA that participate in posttranscriptional gene regulation. However, little is understood about the roles of miRNAs in Alzheimer's disease (AD). In this study, we used next-generation sequencing on RNA extracted from the serum samples of 20 AD patients and 20 controls, yielding a total of 72 miRNAs with significantly changed expression levels. Among these candidates, we selected 9 miRNAs with most significant alteration in disease, and validated their expression levels u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 36 publications
2
53
1
Order By: Relevance
“…Diminished miR-186-3p allows increased BACE1 mRNA translation and cleavage of amyloid peptides that increase the risk for brain disease. miR-19b-3p was reduced in serum from Alzheimer’s patients, and targeted signal transduction and activator of transcription 3 (STAT3) mRNA in a murine model 50 . miR-92a-3p was increased in glioblastoma and targeted BCL2L11 to reduce tumor apoptosis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Diminished miR-186-3p allows increased BACE1 mRNA translation and cleavage of amyloid peptides that increase the risk for brain disease. miR-19b-3p was reduced in serum from Alzheimer’s patients, and targeted signal transduction and activator of transcription 3 (STAT3) mRNA in a murine model 50 . miR-92a-3p was increased in glioblastoma and targeted BCL2L11 to reduce tumor apoptosis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of acute myocardial infarction (AMI), circulating miR-19b-3p was consider to be a promising biomarker for the early phase of AMI [25]. Another study in Alzheimer's disease (AD) indicated that miR-19b-3p was determined to be lower in the serum of AD patients, and the serum level of miR-19b-3p might be a helpful biomarker for AD diagnosis [26]. For sepsis, a variety of abnormally expressed miRNAs have been identified to be associated with the development and progression of sepsis, such as miR-21 and miR-26b [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have observed increased expression of MID1 in Alzheimer’s disease brains [ 74 ]. Our data showing that miR-19b-3p targets MID1 provide one possible explanation for increased expression of MID1 in Alzheimer’s disease tissue, that may be caused by reduced levels of miR-19b-3p [ 72 , 75 ]. Future studies should address if miRNA based therapeutics such as miRNA mimics of the four MID1-targeting miRNAs hsa-miR-19b-3p, hsa-miR-340-5p, hsa-miR-374a-5p and hsa-miR-542-3p could be used to downregulate MID1 in Alzheimer’s disease models and thereby counteract formation of amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%